Publicación Científica Facultad de Odontología • UCR • Nº12 • 2010 15 Promoción de la salud bucal en el adolescente. Estudio comparativo intercolegial, Alajuela 2009 - Campos Arias, Flor (2011)
The present study valued the effectiveness of an educational strategy based on promoting health, directed at adolescents, students from eighth to eleventh grade of the Institute of Alajuela during consecutive four years. The age of the 224 participants was in the range of 16, 5 to 17, 5 years. From that population, 70 eleventh year students formed the case group exposed to the intervention. The control group, not exposed to this experience was constituted by 84 homologous students of the Carmen School and 70 of the Gregorio Jose Ramirez School. For valuation, the results of both groups were compared and favourable changes were demonstrated, mainly cognitive and pragmatic of the Institute of Alajuela students, because a greater percentage of students from this institution (55.7%) took dental brush to the training center; washed their teeth more frequently than the young people of the other schools: 2.4 hours before clinic exam (IC95%: 1,9 - 2.9); knew what the dental plaque was (91%) and knew their effects (90%); used smooth bristles dental brushes (36.2%); they demonstrated that the most important moment to make the oral hygiene was before going to bed (53.3%) and sharing less foods with others (58%). All results showed a statistically significant difference (p ≤ 0.05) when comparing the results of the Institute of Alajuela with the other schools, except those who we e used to share foods. These aspects are important if a change is planned in the future towards improving the oral health in the individual and families